Developing the student's social care character of Islamic Senior High School - Mashito, Dewi; Aziz, Rahmat; Nur Wahyuni, Esa (JIPSINDO, 2023)
This study aims to describe and analyze the activities of teachers and students in schools in developing social care characters. This study uses qualitative methods with the main instruments of observation, interviews, and questionnaires. The subjects in this study were teachers and students in two high schools. Data analysis techniques were carried out through thematic analysis and descriptive analysis. The results of this study stated that the school's success in developing students' socially caring character was due to an understanding of the condition of the student's character. The research results show that schools have a strategic role in developing students' socially caring nature. School efforts to optimize the teacher's role as a supporter of the success of student character development programs have been carried out. The results of this study have implications that character development should begin with identifying students' learning needs. The mixed-method approach can be used as an alternative to perfect research on developing socially caring characters in students.Pengembangan kepedulian sosial siswa di SMA Islam Penelitian bertujuan untuk mengetahui aktivitas guru dan siswa di sekolah dalam pengembangan karakter peduli sosial. Penelitian menggunakan metode kualitatif dengan instrumen utama observasi, wawancara, dan angket. Subyek dalam penelitian ini adalah guru dan siswa di dua SMA. Teknik analisis data dilakukan melalui analisis tematik dan analisis deskriptif. Hasil penelitian menyatakan bahwa keberhasilan sekolah dalam mengembangkan karakter peduli sosial siswa disebabkan oleh pemahaman terhadap kondisi karakter siswa. Sekolah mempunyai peran strategis dalam mengembangkan sifat peduli sosial siswa. Upaya sekolah untuk mengoptimalkan peran guru sebagai pendukung keberhasilan program pengembangan karakter siswa telah dilakukan. Pengembangan karakter hendaknya dimulai dengan mengidentifikasi kebutuhan belajar siswa. Pendekatan metode campuran dapat dijadikan salah satu alternatif penelitian penyempurnaan dalam pengembangan karakter peduli sosial pada siswa.